2021
DOI: 10.3390/en14248356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Change and Occupant Behaviour on the Environmental Impact of the Heating and Cooling Systems of a Real Apartment. A Parametric Study through Life Cycle Assessment

Abstract: Climate change has a strong influence on the energy consumption of buildings, affecting both the heating and cooling demand in the actual and future scenario. In this paper, a life cycle assessment (LCA) was performed to evaluate the influence of both the occupant behaviour and the climate change on the environmental impact of the heating and cooling systems of an apartment located in southern Italy. The analysis was conducted using IPCC GWP and ReCiPe indicators as well as the Ecoinvent database. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Therefore, the influence of climate change has demonstrated that in the future cooling techniques will play an ever-greater role in the buildings' thermal-energy performance. 77,78 Occupants' behaviour inside buildings. Modelling the occupants' behaviour is a challenging task because it is related to several factors involving random, diverse and complex aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the influence of climate change has demonstrated that in the future cooling techniques will play an ever-greater role in the buildings' thermal-energy performance. 77,78 Occupants' behaviour inside buildings. Modelling the occupants' behaviour is a challenging task because it is related to several factors involving random, diverse and complex aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the influence of climate change has demonstrated that in the future cooling techniques will play an ever-greater role in the buildings’ thermal-energy performance. 77,78…”
Section: Introductionmentioning
confidence: 99%
“…Next, regarding research on building retrofits, Fajilla et al [10] conducted a lifecycle assessment to evaluate the impact of climate change and occupant behavior on the environmental performance of heating and cooling systems in an Italian apartment, emphasizing the need for attention to be paid to occupant behavior for future energy strategies. Qi et al [11] investigated the energy-saving potential of lowering heating setpoints in eight cities, discovering significant energy savings even in warm-winter cities, with the mechanism dominated by temperature-difference saving and behavioral saving hours.…”
Section: Introductionmentioning
confidence: 99%